Aksesibilitas Layanan Kesehatan Ibu Dan Anak Di Kawasan Pinggiran Kota Padang: Sebuah Studi Kasus - Qaulan Karima; Rahmat Syahni; Asdi Agustar (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2026)
The Maternal Mortality Rate (MMR) in Indonesia remains one of the highest in Southeast Asia and is still far from the Sustainable Development Goals (SDGs) target. Government efforts to reduce MMR include improving access to quality maternal and child health services, where Puskesmas play a crucial role in providing equitable healthcare and reducing regional disparities. This study aims to describe the accessibility of maternal and child healthcare services and analyze the factors influencing accessibility at Puskesmas Koto Panjang Ikua Koto in an urban fringe area of Padang City. This research employs a quantitative survey method. Data were collected through questionnaires distributed to 100 women of childbearing age. The data were analyzed using descriptive statistics to assess accessibility based on distance and travel time, availability of health facilities and personnel, affordability, and accommodation. The results show that accessibility to maternal and child healthcare services at Puskesmas Koto Panjang Ikua Koto is generally easy. This is indicated by relatively close residential distance, short travel time, adequate availability of health workers and facilities, and affordable services.